Influence of Pharmaceutical Promotional Tools on Doctors' Prescribing Behaviour: An Exploratory Study - Kasliwal, Neeti; Bansal, Ipshita (Indian Journal of Marketing, 2013)
The healthcare industry in general, and the prescription drug industry, in particular, employs an unusual combination of marketing and promotional efforts to influence the doctors who write the prescriptions that determine which drugs (brands) will be used by the ultimate consumer (patient). The involvement of doctors as key decision makers is the reason that they are the focus of most promotional efforts of pharmaceutical companies. Thus, influencing the doctor is a key to the pharmaceutical sales, and the pharmaceutical companies are spending a lot of money on marketing their products to the doctors. The present study examines the impact of promotional tools on doctors' prescribing behaviour. A total of 431 respondents were selected through convenience sampling from different cities of Rajasthan. The results show that the promotional factors which were found to be more influencing were the activities of the MR (medical representative), their rapport with the doctors, their personality traits, and the drug samples, leaflets, and brochures given by the MRs to the doctors. The findings are discussed in the light of past studies, and future directions for research are outlined.